On Supra – Separation Axioms for Supra Topological Spaces - B. K. Mahmoud (Tikrit Journal of Pure Science, 2023)
Through the concepts of supra open sets and supra  we introduce a new class of separation axioms and study some of their properties. We could comparative between these two items. At last we investigate the hereditary and other properties of them